The Impact of Gender Identity on In-Group Trust - Danyliuk, Ivan; Trofimov, Andrii; Vovk, Mariia; Zelenko, Oleksandr; Kutsenko, Yana; Prosina, Olha (International Journal of Criminology and Sociology, 2022)
The article discusses the problem of the influence of gender identity on intra-group trust. Various scientific views on the category of trust are examined. Attention is also paid to the socio-psychological function of trust. Trust, in turn, is the foundation of the relationship between people and a factor in the effectiveness of cooperation. Having defined gender identity, we can say which form of identification positively affects internal group trust, and therefore the effectiveness of cooperation in a sports team. The article describes what type of gender identification (masculinity, femininity, androgyny) positively affects internal group trust, and does this have any connection with the success of a sports team. Also in the article to answer our tasks: 1) conduct a theoretical analysis of foreign and domestic theories of the formation of gender identity; 2) to study the theoretical foundations of the phenomenon of trust and analyze the importance of trust as a component of interpersonal communication in a sports team; 3) conduct a study to determine the gender identity of the person and determine the level of trust in the sports team; 4) analyze the relationship between gender identity and trust in a sports team; 5) to trace the influence of these factors on the success of a football team.